Perbandingan Kekuatan Tekan (Compressive Strength) Resin Komposit Nanofill dengan Teknik Bulk Fill pada Ketebalan yang Berbeda - Rahmawati, Yuliana Siska, drg. Noor Hafida, W.,Sp.KG, drg. Budi Dewantari (2016)
The nanofill composite resin have a mechanical strength equal to hybrid composite resin and a polish quality equal to microfill composite. Compressive strength is one of the most important mechanical factor, due to its role in countering the force produced by mastication in the restoration process. To improve the compressive strength, resin application and material thickness have a significant influence. Bulk fill technique is engineering application of composite resin simultaneously into the cavity. Bulk fill technique is the most frequently used because more efficient and easy. This study is aimed to determine the compressive strength difference of the nanofill composite resin in various thicknesses. This study uses 30 samples of composite resin and divided to 3 groups with a 6 mm diameter. Group I uses nanofill composite resin samples with a thickness of 2 mm, group II uses nanofill composite resin sampels with a thickness of 4 mm and group III uses nanofill composite resin samples with a thickness 6 mm. Samples were soaked in aquades and incubated for 24 hours in a temparature of 370 C. A universal testing machine (UTM) were used to test their compressive strength. Obtained data were analyzed using one-way ANOVA with a 95% CI. The results showed a significant difference between the groups with a p value of 0,000 (p<0,05). The 2 mm thickness nanofill composite resin had the highest compressive strength. We concluded that the 2 mm thickness nanofill composite resin is superior in terms of compressive strength compared to the 4 and 6 mm thickness composite resin.